Maternal oral contraceptive pill use and the risk of atopic diseases in the offspring: A systematic review and meta-analysis. Issue 16 (April 2020) - Bai, Xue-Feng; Wu, Zheng-Xiang; Zhao, Chun-Hong; Wu, Yong; Fei, Chang-Shun; Zhang, Li-Qin; Chen, Zhao-Hui
Abstract : Abstract: Studies of maternal oral contraceptive pill (OCP) exposure and the offspring's risk of atopic diseases are of current interest due to concerns about widespread use of OCP before or during pregnancy. We evaluated whether maternal OCP exposure is associated with an increased risk of atopic diseases by reviewing the literature and performing a meta-analysis. The PubMed and Embase databases were searched to identify potential studies for inclusion. Three common atopic outcomes were included: asthma, eczema, and rhinitis. We found 693 titles, abstracts, and citations, and 6 studies were included in this analysis. A meta-analysis revealed that maternal OCP exposure was associated with higher odds of asthma (odds ratio [OR] 1.1; 95% confidence interval [CI] 1.02–1.19; P  = .014), rhinitis (OR 1.34; 95% CI 1.07–1.68; P  = .011) during childhood, whereas there was no association with eczema (OR 1.17; 95% CI 0.81–1.68; P  = .383). This analysis was limited by the small number of studies included and the limited adjustments for the possible confounders in the studies. Current evidence suggests that maternal OCP exposure increases the risk for respiratory allergic diseases (asthma and rhinitis) in the offspring, but not for eczema. Given the few studies included, future larger, prospective studies that control for important confounders are needed to verify our findings. Abstract : Supplemental Digital Content is available in the text